A new species of Parasesarma (Crustacea: Brachyura: Sesarmidae) from the mangroves of Western Australia - Davie, P. J. F.; Pabriks, L. (Zootaxa, 2010)
A new species of intertidal sesarmid crab, Parasesarma hartogi, is described from the upper mangrove zone in Shark Bay, Western Australia. It differs from its four closest relatives in the P. plictatum species-complex by being broader between the epibranchial angles than between the exorbital angles; showing differences in the number and form of the dorsal dactylar tubercles of the male cheliped, a relatively broader gape between the fingers of the adult male chelae, proportions and shape of the male abdomen, and shape of the male first gonopod.